Social networks as an important part of communication in contemporary trends in adolescents, their impact on their personality and psycho-social behavior - Rugova, Naser (Technium Social Sciences Journal, 2021)
The purpose of this paper is to evaluate the impact of social media on adolescents aged 15-19 years through the qualitative, quantitative, comparative and statistical method, while analyzing, monitoring and evaluating important parameters of the direct effect of these media on the behavior and the building of personality and identity types of these adolescents. This study aims to assess and analyze the level of the impact of social networks on personality traits in 377 adolescents in three high schools of Kosovo where we conducted the research